2022
DOI: 10.4038/jas.v17i2.9740
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Constraints Facing the Agricultural Extension System in Egypt

Abstract: Purpose: The research aimed to identify the important problems facing the agricultural extension system in Egypt. Research Method: A simple random sample was selected from the extension workers in Fayoum and Beheira governorates (196 respondents) Data collection was done from October 2020 to February 2021, using a questionnaire designed based on the framework of modernization and development of agricultural extension systems developed by FAO. Findings: The results indicated that the extension organization in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Beyond such economic incentives, it appears paramount to also increase the social acceptance and recognition of farming for the younger generation [26]. A mean age of wheat farmers of 56 years, compared to the mean age of 26 years of the whole population in Egypt [27], highlights the lack of interest in farming among the younger generation [28]. This trend, if not reversed, may jeopardize the future of agriculture and food production in Egypt and possibly beyond [29].…”
Section: Increasing Wheat Productionmentioning
confidence: 99%
“…Beyond such economic incentives, it appears paramount to also increase the social acceptance and recognition of farming for the younger generation [26]. A mean age of wheat farmers of 56 years, compared to the mean age of 26 years of the whole population in Egypt [27], highlights the lack of interest in farming among the younger generation [28]. This trend, if not reversed, may jeopardize the future of agriculture and food production in Egypt and possibly beyond [29].…”
Section: Increasing Wheat Productionmentioning
confidence: 99%
“…[7] Through its multifaceted functions, which encompass human resource development through training initiatives, it possesses the capacity to contribute significantly to rural development, (14) the adequacy of coordination between agricultural sector departments and agricultural banks in the credit program, the effectiveness of farmers' organizations in transferring modern technology to agricultural areas, and there is a comprehensive and complete approach to agricultural development programs and encouraging the efficiency of agricultural research, extension, and information systems in the agricultural sector. [8,9,10,11,12,13] Agricultural extension serves as a primary instrument to augment agricultural output, promote the welfare of rural households, and elevate their quality of life [14,15] by improving the means of production from both the administrative standpoint and taking care of marketing crops, [16] Furthermore, it facilitates educational transformations by disseminating the outcomes of agricultural research, thereby influencing the knowledge, competencies, and perspectives of farmers and their households. [17] On the other hand, the cultivation of vegetables of all kinds is of great economic importance to some countries because of their export capacity, as they constitute an important part of their national economy, in addition to the short life cycle of the plant, high productivity per unit area compared to other crops, rapid financial returns, and the spread of manufacturing plants.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, studies conducted in many countries around the world, especially in developing countries, confirmed that agricultural extension services were not very effective and suffered from many problems, including weak organizational structures, a central problem, lack of delegation of powers, lack of funding sources, weak operating budget, weak academic programs before service, absence of appropriate training opportunities, lack of a clear and integrated mechanism to link agricultural extension with scientific research institutions, in addition to the absence of coordination with the faculties of agriculture and veterinary medicine, the media, non-governmental organizations, and the private sector. [12,14,15,16,17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%